A 90-day oral toxicity study evaluation of azaphilone derived from Talaromyces amestolkiae: A natural food colorant - Segato, Talita Cristina Mena; Caetano, Erika Leão Ajala; Mott, Rafaella de Barros; Ibanez, Natasha Lien de Almeida; Frattes, Camila da Cunha; Lima, Caio de Azevedo [UNESP]; Alves, Mônica Rodrigues; Santos-Ebinuma, Valéria Carvalho [UNESP]; Grotto, Denise (Elsevier, 2025)
Colorants are widely used in the food industry, especially artificial ones, due to their practicality and low cost. However, some artificial colorants can be harmful to human health. In order to substitute the artificial sources, some microorganisms such as fungi has been highlighted for its production and variety of colorants. The fungus Talaromyces amestolkiae is capable of producing, through its metabolism, colorants classified as azaphilone compounds. The objective of this work was study the sub-chronic (90-day oral) safety evaluation of the novel azaphilone colorant produced by T. amestolkiae in male and female Wistar rats. After a preliminary acute toxicity test, the animals were treated with doses of 250, 500 and 1000 mg/kg body weight via gavage for 90 days. Hematological and biochemical parameters as well as histological examinations were carried out. Oxidative stress was also assessed. Liver damage was observed through an increase in ALT and ALP and confirmed with histological analysis and renal alterations were identified by increased sodium levels and confirmed through histological examination in highest doses, both possibly caused by compounds from the culture medium. Lipid dysregulation, including an increase in triglycerides, was observed at the highest concentrations. Alterations in the Purkinje cells were observed, probably as a consequence of oxidative stress caused by the colorant, but the brain tissue was unaltered. The findings of this study show that the extract containing azaphilone colorants at concentrations higher than 500 mg/mL poses challenges for safe application in food products. However, since the amount of colorant used as a food additive is typically low and tailored to the target color, these results indicate that the extract obtained after cultivation should undergo extraction and purification steps. The dose of 250 mg/kg/bw proved to be safe for both male and female rats, with no or few adverse effects observed.
Keywords: Azaphilone; Natural colorant; Talaromyces amestolkiae; Toxicity